First Observations of GNSS Ionospheric Scintillations From DemoGRAPE Project. Issue 10 (28th October 2016) - Alfonsi, L.; Cilliers, P. J.; Romano, V.; Hunstad, I.; Correia, E.; Linty, N.; Dovis, F.; Terzo, O.; Ruiu, P.; Ward, J.; Riley, P.
Abstract: The Istituto Nazionale di Geofisica e Vulcanologia leads an international project funded by the Italian National Program for Antarctic Research, called Demonstrator of Global Navigation Satellite System (GNSS) Research and Application for Polar Environment (DemoGRAPE), in partnership with Politecnico di Torino, Istituto Superiore Mario Boella, and with South African National Space Agency and the Brazilian National Institute of Space Physics, as key collaborators. DemoGRAPE is a new prototype of support for the satellite navigation in Antarctica. Besides the scientific interest, the accuracy of satellite navigation in Antarctica is of paramount importance since there is always the danger that people and vehicles can fall into a crevasse during a snowstorm, when visibility is limited and travel is restricted to following specified routes using satellite navigation systems. The variability of ionospheric delay and ionospheric scintillation are two of the primary factors which affect the accuracy of satellite navigation. The project will provide a demonstrator of cutting edge technology for the empirical assessment of the ionospheric delay and ionospheric scintillations in the polar regions. The scope of the project includes new equipment for the recording and dissemination of GNSS data and products installed at the South African and Brazilian bases in Antarctica. The new equipment will facilitate the exchange of software and derived products via the Cloud computing technology infrastructure. The project portal is accessible atwww.demogrape.net . We report the first Global Navigation Satellite System (GNSS) signal scintillations observed in Antarctica.